Second-order spectral lineshapes from charged interfaces. Issue 1 (December 2017) - Ohno, Paul; Wang, Hong-fei; Geiger, Franz
Abstract Second-order nonlinear spectroscopy has proven to be a powerful tool in elucidating key chemical and structural characteristics at a variety of interfaces. However, the presence of interfacial potentials may lead to complications regarding the interpretation of second harmonic and vibrational sum frequency generation responses from charged interfaces due to mixing of absorptive and dispersive contributions. Here, we examine by means of mathematical modeling how this interaction influences second-order spectral lineshapes. We discuss our findings in the context of reported nonlinear optical spectra obtained from charged water/air and solid/liquid interfaces and demonstrate the importance of accounting for the interfacial potential-dependentχ (3) term in interpreting lineshapes when seeking molecular information from charged interfaces using second-order spectroscopy. Charged interfaces are important in chemical systems, but the influence of charge on vibrational sum frequency spectra has only recently been considered. Here the authors show the importance of accounting for the interfacial potential-dependent χ(3) term in interpreting spectral lineshapes from charged interfaces.